Molecular characterization of SARS‐CoV‐2 from the saliva of patients in the Republic of Korea in 2020. Issue 6 (3rd October 2022) - Gu, Se Hun; Song, Dong Hyun; Yun, Hyeongseok; Kim, Jung‐Eun; Lee, Seung‐Ho; Lee, Hyunjin; Lee, Tae Ho; Kang, Seol Muk; Jung, Yu Sub; Hur, Gyeunghaeng; Lee, Daesang
Abstract: Background and aims: Despite global vaccination efforts, the number of confirmed cases of coronavirus disease 2019 (COVID‐19) remains high. To overcome the crisis precipitated by the ongoing pandemic, characteristic studies such as virus diagnosis, isolation, and genome analysis of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) are necessary. Herein, we report the isolation and molecular characterization of SARS‐CoV‐2 from the saliva of patients who had tested positive for COVID‐19 at Proving Ground in Taean County, Republic of Korea, in 2020. Methods: We analyzed the whole‐genome sequence of SARS‐CoV‐2 isolated from the saliva samples of patients through next‐generation sequencing. We also successfully isolated SARS‐CoV‐2 from the saliva samples of two patients by using cell culture, which was used to study the cytopathic effects and viral replication in Vero E6 cells. Results: Whole‐genome sequences of the isolates, SARS‐CoV‐2 ADD‐2 and ADD‐4, obtained from saliva were identical, and phylogenetic analysis using Bayesian inference methods showed SARS‐CoV‐2 GH clade (B.1.497) genome‐specific clustering. Typical coronavirus‐like particles, with diameters of 70–120 nm, were observed in the SARS‐CoV‐2 infected Vero E6 cells using transmission electron microscopy. Conclusion: In conclusion, this report provides insights into the molecular diagnosis, isolation, genetic characteristics, and diversity of SARS‐CoV‐2 isolated from the saliva of patients. Further studies are needed to explore and monitor the evolution and characteristics of SARS‐CoV‐2 variants.